Sagittal Plane Correction Using the Lateral Transpsoas Approach: A Biomechanical Study on the Effect of Cage Angle and Surgical Technique on Segmental Lordosis. Issue 17 (September 2016) - Melikian, Rojeh; Yoon, Sangwook Tim; Kim, Jin Young; Park, Kun Young; Yoon, Caroline; Hutton, William
Abstract : Study Design: Cadaveric biomechanical study. Objective: To determine the degree of segmental correction that can be achieved through lateral transpsoas approach by varying cage angle and adding anterior longitudinal ligament (ALL) release and posterior element resection. Summary of Background Data: Lordotic cage insertion through the lateral transpsoas approach is being used increasingly for restoration of sagittal alignment. However, the degree of correction achieved by varying cage angle and ALL release and posterior element resection is not well defined. Methods: Thirteen lumbar motion segments between L1 and L5 were dissected into single motion segments. Segmental angles and disk heights were measured under both 50 N and 500 N compressive loads under the following conditions: intact specimen, discectomy (collapsed disk simulation), insertion of parallel cage, 10° cage, 30° cage with ALL release, 30° cage with ALL release and spinous process (SP) resection, 30° cage with ALL release, SP resection, facetectomy, and compression with pedicle screws. Results: Segmental lordosis was not increased by either parallel or 10° cages as compared with intact disks, and contributed small amounts of lordosis when compared with the collapsed disk condition. Placement of 30° cages with ALL release increased segmental lordosis by 10.5°. Adding SP resection increased lordosis to 12.4°. Facetectomy and compression with pedicle screws further increased lordosis to approximately 26°. No interventions resulted in a decrease in either anterior or posterior disk height. Conclusion: Insertion of a parallel or 10° cage has little effect on lordosis. A 30° cage insertion with ALL release resulted in a modest increase in lordosis (10.5°). The addition of SP resection and facetectomy was needed to obtain a larger amount of correction (26°). None of the cages, including the 30° lordotic cage, caused a decrease in posterior disk height suggesting hyperlordotic cages do not cause foraminal stenosis. Level of Evidence: N/A